Can Arginine Help to Improve Milk Supply in Humans? It Does in Cows - Luoyang Ding; Yizhao Shen; Tianyou Wu; Lianmin Chen; Juan J. Loor; Shane K. Maloney; Mengzhi Wang; Dominique Blache (Proceedings, 2023)
Arginine can be metabolized into nitric oxide, polyamine, creatine, or agmatine, and each of those metabolites has several biological functions [...]